2009
DOI: 10.4049/jimmunol.0901530
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of JNK-Mediated Phosphorylation for Translocation of Group IVA Phospholipase A2 to Phagosomes in Human Macrophages

Abstract: Eicosanoids are a broad family of lipids that play a critical role in host defense against bacterial and fungal infections. The first enzyme in the metabolic pathway for the generation of eicosanoids is group IVA phospholipase A2, also known as cytosolic phospholipase A2α (cPLA2α). During phagocytosis, cPLA2α has been found to translocate to the phagosome, although the molecular mechanism involved in such a translocation has not been elucidated. By using enhanced GFP-tagged proteins we show in this work that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 66 publications
0
52
0
2
Order By: Relevance
“…In this regard, it is striking that sPLA 2 -V translocates to the forming phagosome in zymosan-stimulated murine macrophages (50, 66) but not in zymosan-stimulated human macrophages (33,34). These data suggest that, at least in humans, the regulatory actions of the enzyme on the phagocytosis process itself occur at a level distinct from that of the phagosome, probably at the plasma membrane level.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this regard, it is striking that sPLA 2 -V translocates to the forming phagosome in zymosan-stimulated murine macrophages (50, 66) but not in zymosan-stimulated human macrophages (33,34). These data suggest that, at least in humans, the regulatory actions of the enzyme on the phagocytosis process itself occur at a level distinct from that of the phagosome, probably at the plasma membrane level.…”
Section: Discussionmentioning
confidence: 78%
“…It should be noted that human macrophages are relatively large cells (diameter . 30 mm) (33,34); hence, their membrane phospholipid content is quite high (35). Thus, if the hydrolytic action of IL-4-induced sPLA 2 -V on membrane phospholipids is limited, the small changes involved easily could be obscured by the high phospholipid amount present in the cells.…”
Section: Spla 2 -V-dependent Changes In Lipid Metabolism In Il-4-treamentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (35) showed that secretion of monocyte chemoattractant protein-1 induced by stimulation of macrophages with synthetic oligodeoxynucleotides containing CpG motifs depends on cPLA 2 ␣ activity, which can be blocked by pharmacological inhibition or down-regulation of JNK. Casas et al (36), on the other hand, showed that translocation of cPLA 2 ␣ to phagosomal membranes of macrophages, an event required for eicosanoid generation and killing of the ingested microbe, requires enzyme phosphorylation at Ser-505 and is blocked after pharmacological inhibition of JNK. Therefore, this study describes for the first time the crucial role of the JNK cascade in the activation of cPLA 2 ␣ for LD biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the phosphorylation of PLA 2 IV␣ in induction of membrane translocation is not fully defined, although a requirement for PLA 2 IV␣ phosphorylation for its full enzymatic activation has been reported by different groups (15,21,22). Serine phosphorylation on PLA 2 IV␣ (Ser-505 or Ser-727) is mediated mainly by the mitogen-activated protein kinases (MAPKs) ERK1/2, and by the stress kinases p38 and JNK, and this has been shown to increase the intrinsic enzymatic activity of PLA 2 IV␣ (23,24).…”
mentioning
confidence: 99%